The runaway dolls - Martin, Ann M., 1955-; Godwin, Laura; Selznick, Brian (New York : Hyperion Books for Children, 2008)
Best friends Annabelle and Tiffany risk placing all of dollkind in danger when they run away while trying to prevent Tilly from being sent back to London before they can determine if she is Annabelle's long-lost baby sister.
Ages 8-12.
Middle School.
730
Accelerated Reader
Reading Counts!
Accelerated Reader AR
Keywords: Vaughan, Brian K. -- Juvenile fiction; Runaways (Vaughan, Brian K.); Dolls -- Juvenile fiction; Missing children -- Juvenile fiction; Runaway children -- Juvenile literature; Dolls -- Fiction; Lost children -- Fiction; Runaways -- Fiction; JUVENILE FICTION -- Social Themes -- Runaways; JUVENILE FICTION -- Toys, Dolls & Puppets; Dolls; Missing children; Runaway children; Dolls -- Fiction; Missing children -- Fiction; Missing persons -- Fiction; Novels; Fiction; Juvenile works; Fantasy fiction; Novels